To develop values in the first childhood: a proposal of pedagogic action - Paula Maria Santos Koeric; Thais Carboni Martins (Universidade Federal de Santa Catarina, 2005)
In this article the authors present reflections and they look for to address our glance to the children, privileging the infantile manifestations in your singularities and diversities, in order to we understand your Real desires and needs. I tell of an experience of doing them if they question on your relationships and they formulate your own judgements on what it is right or wrong.